Optimalisasi Pencahayaan Alami di Pasar Batu Raja, Kec.Wasilei, Kabupaten Halmahera Timur - Utdin Furqon Amali; Sherly Asriany; Mohamad Jamil (Asosiasi Dosen Muda Indonesia, 2025)
Batu Raja Market is in UPT. Subaim SP.2. This market is located at 1°04'38